Dampak Digitalisasi Terhadap Kualitas Pelayanan Publik dan Barang Publik: Penelitian - Jemelly Prisya Simajuntak; Raymon Pernando Pasaribu; Yesi Veronika Simarmata; Ledi Marina Purba; Diana Winata Lumban Gaol (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine how digitalization impacts the quality of public services and the delivery of public goods in Indonesia, while identifying the factors that facilitate and hinder them. The approach used is descriptive qualitative, using a case study within a government agency such as the Medan Population Service. Data collection involved analyzing the policy document Presidential Regulation No. 95 of 2018, impact matrix tables, and process flow diagrams, using the Miles and Huberman analytical framework, which includes data reduction, presentation, and formulation of conclusions. The results show that digitalization significantly improves efficiency: service time is reduced from several days to 30 minutes, operational costs decrease by 40 percent due to transparent e-procurement, data accuracy reaches 98 percent, and public satisfaction increases by 82 percent due to the convenience provided by the SPBE and INA Digital applications. Transparency is increased with a 60 percent reduction in problematic procurement cases through real-time audits; However, issues such as inadequate internet infrastructure (20-30 percent effectiveness in rural areas), low digital literacy among the elderly, and concerns about data security continue to hamper the accessibility of public goods such as telemedicine and targeted social assistance.